Perforating granuloma annulare mimicking papulonecrotic tuberculid - Amanda Regio Pereira; Mariana Bellini Vieira; Marina Pinhas Ariza Monteiro; Milvia Maria Simões e Silva Enokihara; Nilceo Schwery Michalany; Ediléia Bagatin; Karime Marques Hassun (Sociedade Brasileira de Dermatologia, 2013)
A case is reported of a patient presenting lymph node tuberculosis and cutaneous lesions resembling papulonecrotic tuberculid, but histologically compatible with perforating granuloma annulare and which responded satisfactorily to antituberculous therapy. This is probably one of the first reports of the association of perforating granuloma annulare and tuberculosis, and it is important therefore to highlight the relevance of this disorder in the differential diagnosis of papulonecrotic tuberculid and to raise the hypothesis that this entity should also be considered to be a variant of tuberculid.